Pengembangan Aplikasi Pembelajaran Interaktif Olahraga Bodyweight Trainning di Rumah Berbasis Android dengan Metode Multimedia Development Life Cycle - Adi Purnomo; SM. Santi Winarsih; Omega Rimba Gemilang (Universitas Boyolali, 2022)
In this study, an Android-Based Home Workout Interactive Learning Application was made with the Multimedia Development Life Cycle Method. This Home Workout application is used to help beginners who want to exercise during this pandemic in learning daily exercise movements at home with minimal equipment. Making this Android-Based Home Workout Interactive Learning application using android studio and XML. XML is used to create user interfaces. Application design uses UML (Unified Modeling Language) modeling, which includes diagrams such as Activity Diagrams, Sequence Diagrams, Class Diagrams, Use Case Diagrams. The use of Android is because Android is currently used by some Indonesian people and even the world and the technology is classified as the latest technology. This Home Workout Interactive Learning application will display menus such as muscle groups, full body menus, training schedules, and quizzes. With this android-based application, users will be more interested and easy to learn. Keywords— Workout, Interactive, muscle